Intimate Partner Violence during the Index Pregnancy and its correlates among a panel of pregnant women in Ethiopia, evidence from performance, and monitoring for action (PMA) 2021 cohort two baseline survey - Solomon Abrha Damtew; Solomon Shiferaw; Assefa Seme; Bezawork Ayele Kassa; Fitsum Tariku Fantaye; Addisalem Zebene Armdie; Seifu Yinneda Berhe; Desalegn Getachew Nerisho; Ayanaw Amogne; Mahari Yihdego Gidey; Niguse Tadele Atnafu (BMC Pregnancy and Childbirth)
Abstract Introduction Current intimate partner violence (IPV) in Ethiopia is considerably high. This study aimed at determining the prevalence of IPV among a panel of pregnant women during their index pregnancy and identify its correlates using Performance Monitoring for action (PMA) cohort 2 baseline data. Documenting the magnitude of IPV thus far during the index pregnancy and identifying factors affecting it contributes its share for the ministry and relevant developmental partners in tracking progress towards eliminating all forms of violence against women and girls by 2030. Methods We conducted a further analysis of national level follow up secondary data sets from Performance Monitoring for action Ethiopian (E_PMA). This study used PMA cohort two baseline data which enrolled pregnant and recently postpartum women and collected real time data on various sexual, reproductive, maternal and new born nationwide priority indicators using customized Open Data Kit Mobile application. These data were collected using standard pretested questionnaire prepared in three local languages (Amharic, Afan Oromo and Tigrigna) by well experienced resident enumerators. This study was restricted to 1,796 pregnant women at the enrollment. Frequency was computed to describe the study participant’s characteristics, and chi-square statistics was used to assess cell sample size adequacy. Multilevel binary logistics regression model building process was employed to identify correlates of IPV. Results were presented in the form percentages and odds ratio with 95% Confidence Intervals. Candidate variables were selected using p-value of 0.25. Statistical significance was declared at p-value of 0.05. Results One in six; 16.7% (14.81%, 18.76%) pregnant women have reported experiencing at least one form of physical and/or sexual IPV thus far in their index pregnancy. The prevalence of encountering at least one form of sexual violence was 12.53% (10.91%, 14.35%) while 7% (5.5%, 8.3%) of them experienced at least one form physical intimate partner violence thus far during their index pregnancy. Women perceived risk about contraceptive use ((AOR: 95% CI: 1.66 (1.10, 2.47)), higher birth order ((AOR: 95% CI: 1.88 (1.05, 3.34)), unhappy emotional fertility intention when learned their index pregnancy ((AOR: 95% CI: 1.7 (1.02, 2.84)) and a family size of 4 to 5 ((AOR: 95% CI: 1.87 (1.11. 3.14)) were the fixed effects factors found to increase the odds of IPV significantly and positively. On the contrary, being in the third trimester of gestation at enrollment was another fixed effect variable which contributed for the 44% lower odds ((AOR: 95% CI: 0.56 (0.34, 0.92)) of experiencing IPV thus far in their index pregnancy. Conclusions The overall burden of IPV reported was high; with nearly double the percentage of women experiencing sexual violence during the index pregnancy compared to physical IPV. More work needs to be done to achieve zero tolerance against any form of violence among women and girls in general and among pregnant women in particular. Efforts targeted in improving women perception on issue related with their contraceptive use, counseling women on how to prevent IPV during their antenatal care (ANC) visit along with advising the use of inter pregnancy contraception and empowering them to control on their fertility are hoped to mitigate such considerably higher odds of IPV among pregnant women. Further programs and intervention on awareness creation towards the misconception that women held about contraceptive use would contribute much. These activities and efforts need to target younger women. The implication of the findings calls key actors and the Federal Democratic Republic of Ethiopia Health Minster to design and implement programs on women emotional fertility readiness and empowering them to control over their fertility through diversified contraceptive provision which is critical in combating the reported substantial IPV experience during pregnancy. Creating institutional capacity in the health system through strengthening and expanding one stop centers to provide medical treatment, care, and psychosocial support for victims and survivors could play a pivotal role. In addition, installing rapid referral system and linkage to the legal system could play a vital role. Moreover, working on early marriage and counseling on childbirth; and spaced pregnancy for those young couples is imperative. Further implication of this study was installing contraceptive and violence related preconception care packages in the health system is very critical in the combat against IPV and any form of gender based violence.